2005
DOI: 10.1111/j.1540-8159.2005.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic Incompetence in Patients with an Implantable Cardioverter Defibrillator: Prevalence and Predicting Factors

Abstract: Chronotropic incompetence (CI), which has not been systematically examined in the ICD patient population, may have implications for device programming. A total of 123 ICD patients were classified into three groups: single-chamber ICD with sinus rhythm, dual-chamber ICD with sinus rhythm, and single-chamber ICD with permanent atrial fibrillation. Heart rate response, maximum oxygen uptake, and oxygen uptake at the anaerobic threshold were measured during treadmill exercise testing. In addition, clinical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…17 The INTRINSIC RV study accomplished this goal. Algorithms other than AVSH exist 29 to reduce ventricular pacing in dual-chamber ICDs; however, no other large randomized, prospective study has shown clinical benefits as were shown in the present study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…17 The INTRINSIC RV study accomplished this goal. Algorithms other than AVSH exist 29 to reduce ventricular pacing in dual-chamber ICDs; however, no other large randomized, prospective study has shown clinical benefits as were shown in the present study.…”
Section: Discussionmentioning
confidence: 77%
“…Rate-responsive pacing has been demonstrated to improve cardiovascular exercise response in pacemaker patients 14,15 and heart failure patients receiving cardiac resynchronization therapy. 16 A recent study reported a 38% incidence of chronotropic incompetence in ICD recipients, 17 but the utility of rate-adaptive pacing has not been studied in this population.…”
Section: Clinical Perspective P 16mentioning
confidence: 99%
“…In this context, the DAVID II trial 36 showed no differences in outcome in ICD patients who were AAI programmed versus those with VVI back‐up pacing, but it is difficult to accept AAI pacing only in ICD recipients if we consider the potential need for an extra ventricular pacing support in this population over time. SND and AV troubles characterize the clinical course of ICD patients, linked with spontaneous evolution of the disease and progression of AV conduction disturbances combined with an eventually increasing need for β‐blocking therapy or introduction of amiodarone for ventricular or supraventricular arrhythmias 41–43 …”
Section: Effects Of Rv Pacing In Icd Recipients With Low Lvefmentioning
confidence: 99%
“…Depending on the definition used, CI has been identified in anywhere from 9% to 84% of patients [4][5][6][7][8][9][10] and has been associated with adverse outcomes and poor prognosis [11][12][13][14]. CI in paced patients has been associated with reduced VO 2 [9,15] while rate responsive programming in these patients has been associated with improvement in exercise tolerance [16,17].…”
Section: Introductionmentioning
confidence: 97%